Cutting Indium Usage by 60% in SHJ-Modules Maintaining High Efficiency - Sebastian Pingel; Ioan Voicu Vulcanean; Charlotte Röhnelt; Winfried Wolke; Vasileios Georgiou-Sarlikiotis; Alexander Krieg; Martin Bivour; Anamaria Steinmetz (SiliconPV Conference Proceedings)
In this work the impact of reducing the Indium consumption for SHJ cells and modules is investigated. Optical simulations show that thinner Indium Tin Oxide (ITO) layers can be used on module level with minor reflection losses while on cell level losses are more severe. For extremely thin ITO layers with a thickness of 7-28 nm on texture a dielectric layer is necessary to maintain / improve the JSC level on both cell and module levels. Results (i) on solar cells (Transfer Length Method - TLM) for lateral resistance and (ii) on shunt structures for vertical electrical resistance showed that there is significant improvement potential if the doping of the layers is adapted parallel to thickness reduction. Solar cell samples with 60% reduced ITO layer thickness on front and rear sides show a similar series resistance level as the 70 nm reference but lower JSC. Optical simulation showed that module integration will recover most of the lost JSC resulting in an expected 0.5%abs. efficiency loss for samples with total (front & rear side) 60% less Indium without adding any process steps. Applying an additional dielectric film enables 80% Indium reduction on the front side with JSC gain on cell level and similar JSC on module level compared to the ITO with reference thickness.